PENGARUH TRUST TERHADAP NIAT ULANG BERWAKAF UANG PADA BADAN WAKAF AL QUR’AN SURABAYA MELALUI BELIEF - Hesti Dwi Fandini; Ririn Tri Ratnasari (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the effect of trust on the repeat intention to give cash waqf at BWA Surabaya through beliefs which include aspects of attitude, subjective norms, and perceived behavioral control. Retrieval of data in this study using a questionnaire with a total sample obtained by 35 waqif, who had already given money endowment at BWA Surabaya in one past year. The sampling technique are both non probability and simple random sampling. This research uses a quantitative approach with path analysis techniques. The endogenous variable in this study is the repeat intention to give cash waqf, while the exogenous variable used is trust and the intervening endogenous variable is beliefs. The results of this study showed that trust has a positive and significant influence on beliefs. Nevertheless, trusts does not affect the repeat intention to give cash waqf. However, trusts indirectly affects to the repeat intention to give cash waqf through beliefs variables that have a positive and significant effect on the repeat intention to give cash waqf at BWA Surabaya. Suggestions for BWA Surabaya should be maintaining and increasing trusts and beliefs of waqif which can increase the repeat intention of waqif to give cash waqf at BWA Surabaya.Keywords: Trust, Wakaf, Belief